Oseltamivir analogs with potent anti-influenza virus activity. Issue 8 (August 2020) - Kumar, Sumit; Goicoechea, Steven; Kumar, Sonu; Pearce, Catherine M.; Durvasula, Ravi; Kempaiah, Prakasha; Rathi, Brijesh; Poonam,
Highlights: Despite of vaccines, therapeutics are critically important to keep check on evolving virulence from mutations. Oseltamivir remains a single effective oral drug against influenza infections. High potency of guanidino-oseltamivir carboxylate is compromised due to poor oral bioavailability. Viral neuraminidase represents a key target for the discovery of new OS analogs due to its essentiality. Abstract : Influenza A and B viruses cause seasonal worldwide influenza epidemics each winter, and are a major public health concern and cause of morbidity and mortality. A substantial reduction in influenza-related deaths can be attributed to both vaccination and administration of oseltamivir (OS), which is approved for oral administration and inhibits viral neuraminidase (NA), a transmembrane protein. OS carboxylate (OSC), the active form of OS, is formed by the action of endogenous esterase, which targets NA and is shown to significantly reduce influenza-related deaths. However, the development of resistance in various viral variants, including H3N2 and H5N1, has raised concern about the effectiveness of OS. This comprehensive review covers a range of OS analogs shown to be effective against influenza virus, comparing different types of substituent group that contribute to the activity and bioavailability of these compounds. Teaser: Oseltamivir, a single effective oral drug available for the treatment of influenza infections, makes the discovery of its analogs valuable and interesting.